Corporate governance, audit quality and firm performance – an empirical evidence - Quang Minh Nguyen; Chien V. Nguyen (Cogent Economics & Finance, 2024)
The purpose of the study is to assess the impact of governance capacity and audit quality on the financial performance of enterprises listed on the Vietnam Stock Exchange in the period 2012 to 2021, including 40 selected enterprises, this is a complete stage of development of Vietnam's stock market including the addition of bond market and derivatives market. Data is collected annually from audited financial statements, annual reports, prospectus. The paper deploys the panel data regression methods such as Pooled OLS, FEM and REM, and the feasible generalized least squares (FGLS); and evaluates the possibility of interdependence between enterprises as well as test the possibility of endogenous phenomena in the research model. Research results confirm that board size has a negative impact on the financial performance of the business, in contrast, the participation of women on the board and the selection of men as CEO have a positive effect on corporate profits. Research results also suggest that enhancement of audit quality can improve corporate performance. In addition, businesses should seek funding by equity, or in the case of debt, businesses should use short-term debt to help them its increase financial efficiency. Finally, the study confirms that large enterprises or enterprises investing in fixed assets have the ability to generate higher profits. Thereby creating a basis for enterprises listed on the Vietnam Stock Exchange to improve operational efficiency. The effective functioning of the board of directors can help the business become more efficient, and this result is better if the business has the ability to choose a reputable auditor. In the case of Vietnam, businesses have an increasingly important position in contributing to the country's socio-economic development, so evaluating the effectiveness of the board of directors becomes necessary. Research results demonstrated that board size has a negative impact on the financial performance, in contrast, the participation of women on the board and the selection of men as CEO have a positive effect on corporate profits. In addition, enhancement of audit quality can improve corporate performance. A firm should seek funding by equity, or in the case of debt, businesses should use short-term debt to increase its financial efficiency. Further, large enterprises or enterprises investing in fixed assets have the ability to generate higher profits.
Keywords: 330; Audit quality; board ofdirectors; corporategovernance; endogeneity; firm performance